PENGARUH PENGGUNAAN PRIMER TERHADAP DAYA TAHAN MAKEUP PADA WAJAH BERMINYAK - Nurhayati, Ifa; Maghfiroh, Anik; Yanuarti, Happy; Zulfa, Nadira Fathia; Nuramalia, alla Arrika (Journal of Beauty and Cosmetology (JBC), 2025)
Abstract Primer is one of the cosmetic products used as a base before applying makeup, serves to smooth the skin texture and increase the durability of makeup. Oily skin is often a challenge in maintaining the appearance of makeup so that it remains durable, even, and does not fade easily due to excess sebum production. This study aims to determine the effect of primer use on the durability of makeup, especially on oily skin types. The method used is a descriptive qualitative approach through observations of five female subjects aged 20-30 years with oily skin, as well as in-depth interviews with two professional makeup artists. The results of the study showed that consistent use of primer can extend the durability of makeup up to eight hours, reduce excess shine in the T-zone area, and provide a smoother and matte finish. This study is expected to be a practical reference for consumers and makeup professionals in choosing and applying primers that suit their skin needs. Keywords: oily skin, primer, makeup